2022
DOI: 10.1016/j.asmr.2021.11.010
|View full text |Cite
|
Sign up to set email alerts
|

Rotator Cuff Repair in the Pediatric Population Displays Favorable Outcomes: A Systematic Review

Abstract: To systematically review the literature to determine the injury mechanisms, presentation, and timing of diagnosis for pediatric patients with intratendinous rotator cuff tears and to determine the efficacy of surgical intervention for affected patients. Methods: PubMed, Cumulative Index to Nursing and Allied Health Literature (CINAHL), and Scopus were searched. Studies were included if they involved only pediatric patients, soft-tissue rotator cuff injuries managed surgically, and reported outcomes. Patient ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 53 publications
0
6
0
Order By: Relevance
“… 39 , 40 Clinical outcomes for surgical repair of rotator cuff tears in pediatric patients have been reported to be excellent, but these studies have not independently reported outcomes for open and arthroscopic repair. 41 , 42 Only one study included in this review, Eisner et al., 26 evaluated clinical outcomes of partial-thickness rotator cuff tears treated with arthroscopic repair but did not obtain preoperative scores and was thus unable to quantify the clinical benefit of arthroscopic repair. Arthroscopy for obstetric brachial plexus birth palsy resulted in improved Mallet, glenoid retroversion, PHHA glenoid deformity score, and external rotation after surgery consistent with previous systematic reviews.…”
Section: Discussionmentioning
confidence: 99%
“… 39 , 40 Clinical outcomes for surgical repair of rotator cuff tears in pediatric patients have been reported to be excellent, but these studies have not independently reported outcomes for open and arthroscopic repair. 41 , 42 Only one study included in this review, Eisner et al., 26 evaluated clinical outcomes of partial-thickness rotator cuff tears treated with arthroscopic repair but did not obtain preoperative scores and was thus unable to quantify the clinical benefit of arthroscopic repair. Arthroscopy for obstetric brachial plexus birth palsy resulted in improved Mallet, glenoid retroversion, PHHA glenoid deformity score, and external rotation after surgery consistent with previous systematic reviews.…”
Section: Discussionmentioning
confidence: 99%
“…22 Surgery may improve pain and function; the current remaining goal might be developing better rehabilitation programs to help these patients return to play. Condron et al, 13 in a systematic review, report excellent outcomes whether surgery was performed within 1 month of injury or delayed for up to 2 years. This result might contradict the conventional approach suggesting an early surgical management is crucial for traumatic injuries to prevent atrophy and scar tissue formation.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, radiographs could demonstrate indirect signs of RC tears, such as a halo of calcification superior to the humeral head, in the subacromial space correlated to a long-standing supraspinatus injury. 13 Ultrasound can also be used as a diagnostic tool for RC tears in young patients. It is noninvasive, cost-effective, and readily available.…”
Section: Diagnosismentioning
confidence: 99%
See 2 more Smart Citations